1989
DOI: 10.1002/abio.370090111
|View full text |Cite
|
Sign up to set email alerts
|

Influence of B‐vitamins and trace elements on lysine production by micrococcus varians 2Fa

Abstract: A hydrocarbon utilizing strain of iVicrococcus vuriuns 2Fa isolated from local soil has been found to yield lysine 2.6 g 1-l. Addition of B-vitamins and trace elements to the optimal media, has been found to stimulate growth and enhance lysine yield. KINOSHITA [l] isolated a glutamic acid producing Micrococcus glutamicus ever since microbial production of amino acid has become an established branch of industrial microbiology. Among the other amino acids, microbial production of lysine has been extensively stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…There are no reports on the effect of antibiotics on methionine production. [9,17] have reported increased amino acid production in the presence of small quantities of several kinds of antibiotics, although the exact role played by these antibiotics is not clearly understood. [18] suggested that a change in permeability of the cell wall caused by antibiotics may be responsible for improved yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no reports on the effect of antibiotics on methionine production. [9,17] have reported increased amino acid production in the presence of small quantities of several kinds of antibiotics, although the exact role played by these antibiotics is not clearly understood. [18] suggested that a change in permeability of the cell wall caused by antibiotics may be responsible for improved yield.…”
Section: Resultsmentioning
confidence: 99%
“…However, alteration of these mechanisms can lead to L-methionine accumulation [6,7]. The influence of antibiotics and surfactants on amino acid production by bacterial organism has been reported [8][9][10][11] although the exact role played by these antibiotics and surfactants are not clearly understood. In our previous work, we reported the production of L-methionine by three methionine yielding strains of Bacillus cereus isolated from different soil ecovars in Owerri, Nigeria [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…No production of lysine by Microbacterium species has been reported. Although Sen and Chatterjee [20], Ekwealor and Obeta [18] noted that the yielding strains are found mostly among species of Arthrobacter, Corynebacterium, Brevibacterium and Bacillus.…”
Section: Discussionmentioning
confidence: 99%
“…These isolates produced lysine on solid medium and were termed lysine producers. 20.0 g and (NH 4 ) 2 SO 4 , 10.0 g; served as a carbon and nitrogen sources respectively, and the medium sterilized at 115˚C for 10 min. one milliliter volume of the seed inoculum (Ca 5.6 × 10 8 cells/ml) was inoculated into duplicate 100 ml Erlenmeyer flask containing 20 ml of fermentation medium.…”
Section: Preliminary Screening Of Isolates For Lysine Production On Smentioning
confidence: 99%
“…Tani et al [27], reported a high methionine yield when 200 µg/l thiamine was added to the fermentation medium in methylotrophic yeast, Candida biodinii. Sen and Chatterjee [28], noted that thiamine HCl stimulated lysine accumula- tion in Micrococcus varians 2fa. Ekwealor and Obeta [29], reported improved lysine yields in Bacillus megaterium SP 86 and Bacillus megaterium SP 76 with the addition of 10 µg/ml and 100 µg/ml of folic acid and riboflavin respectively.…”
Section: Resultsmentioning
confidence: 99%